The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1371/journal.pone.0155956
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Periodontitis in Patients with Established Rheumatoid Arthritis: A Swedish Population Based Case-Control Study

Abstract: IntroductionThe possible hypothesis of a link between periodontitis and rheumatoid arthritis (RA), specifically anti-citrullinated protein antibody (ACPA) positive RA, prompted us to investigate the prevalence of periodontitis in the Swedish Epidemiological Investigation of RA (EIRA), a well-characterised population-based RA case-control cohort.MethodsPeriodontal status of 2,740 RA cases and 3,942 matched controls was retrieved through linking EIRA with the National Dental Health Registry (DHR), where dental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 62 publications
3
63
3
2
Order By: Relevance
“…Furthermore, citrullinated proteins have been detected in both rheumatoid joints and inflamed gingival tissue, as well as in other tissues in relation to inflammatory conditions [1719]. However, an association between PD and established RA could not be confirmed in one of our recent publications [20]. …”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, citrullinated proteins have been detected in both rheumatoid joints and inflamed gingival tissue, as well as in other tissues in relation to inflammatory conditions [1719]. However, an association between PD and established RA could not be confirmed in one of our recent publications [20]. …”
Section: Introductionmentioning
confidence: 94%
“…Individuals with rheumatoid arthritis have an increased risk of gingivitis and periodontitis (certainty low) and those with Sj€ ogren's syndrome appear to experience higher levels of periodontal diseases (certainty very low) (Antoniazzi et al 2009, Eriksson et al 2016, Fuggle et al 2016, Le Gall et al 2016). …”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…For rheumatoid arthritis, the association with periodontitis may be traced to the early 19th century, when Benjamin Rush (an American physician and politician) reported that total tooth eradication was a cure for Brheuma^; this Btreatment^was in use until the mid-20th century [87]. A 2016 review of dental records confirmed that 90 % of RA patients in the adult Swedish population had a diagnosis of periodontitis [88]; however, there was no significant difference in the prevalence of periodontitis in patients with established RA compared to healthy controls. Okida et al [89] showed that several periodontopathic bacteria were associated with RA, and Persson summarized evidence that associated these bacteria with RA [87].…”
Section: Periodontal Infections Smoking and Aplmentioning
confidence: 99%